Assessment and rehabilitation of the damaged historic Cenabı Ahmet Pasha Mosque. (November 2015) - Koseoglu, Gulsum Cagil; Canbay, Erdem
Abstract: Historic structures form a very important part of our cultural heritage and are supposed to be preserved properly. Therefore, full comprehension of the structural behavior of historic structures is of prior importance. In this study, a damaged single domed mosque of 16th century classical Ottoman Architecture has been investigated. Serious damage was recorded at various locations and structural elements including the dome and the structural masonry walls, as a result of which the structure was recently closed to worshippers and visitors. The mosque was constructed in the 16th century on silty–clay soil. Due to local drought conditions in the last couple of decades, the water table has changed excessively, causing soil displacements that have especially affected the masonry structure. The main objective of the present study is to explore the reasons for the structural damage and to propose a rehabilitation method suitable for the amelioration of the observed damage. The results of the structural analyses conducted have been compared with the observed damage and some rehabilitation methods have been proposed accordingly. These methods include mini-pile application proceeding as far as the firm soil (rock) in order to prevent the soil displacement. Furthermore, as the cracks on the masonry walls would be repaired using materials that would be in conformity with the structure's historical texture, it has been proposed that a steel ring be fitted suitably around the damaged dome's base in order to contain further propagation of cracks. Highlights: Finite Element Model of a historic masonry mosque is constituted. Serious structural cracks were identified on the masonry mosque. Finite element modeling is used based on field observations and ground data to understand the cause of the structural damage. The behavior of the masonry structure is simulated under gravity and seismic loads. Relation between the damage on the structure and the FEM analysis results are compared.